Socio-demographic and economic inequalities in modern contraception in 11 low- and middle-income countries: an analysis of the PMA2020 surveys - Blumenberg, Cauane (Reprod Health, 2020)
BACKGROUND: Contraception is a key component of sustainable development, empowering women, reducing the risk of maternal and child mortality and promoting economic growth. It is part of the Sustainable Development Goals agenda, where the aim is to achieve universal access to sexual and reproductive health. Our objective was to evaluate trends and inequalities in modern contraceptive prevalence, and according to the type of modern contraceptive, in 11 low- and middle-income countries that are partners of the Family Planning 2020 initiative. METHODS: Analyses were performed using 62 Performance Monitoring and Accountability 2020 (PMA2020) surveys from 11 countries. Forty surveys were nationally representative, while 22 had regional coverage. Regional surveys were analyzed separately, totalizing 15 geographies from 11 countries. We described trends on modern contraceptive prevalence, and its subtypes (short- and long-acting reversible contraceptives, and permanent methods), by calculating absolute average annual changes. Absolute inequalities on the prevalence of modern contraceptives were assessed for the most recent survey of each geography using the slope index of inequality, and according to wealth, education and age. RESULTS: The overall prevalence of modern contraception increased in most geographies analyzed, reaching a 7.2 percentage points increase per year in Lagos, Nigeria. This increase was mostly influenced by the long-acting reversible contraceptives, which increased in 73% of the geographies. Although the largest share of modern contraception is represented by short-acting reversible contraceptives, these are reducing and giving space for the long-acting methods. The exception was Rajasthan, India, where the permanent methods accounted for 70% of the modern contraception share, and their prevalence was almost 40%. Inequalities were identified in favor of richer, older and better educated women. CONCLUSIONS: Out of the 15 geographies analyzed, 11 demonstrated an increase in overall modern contraceptive use – mainly driven by the uptake of long-acting reversible contraception. However, even in the groups with the highest prevalence, modern contraceptive use was at most 60% in most geographies. So, we are far from reaching the desired universal coverage proposed by the Sustainable Development Goals.